ANALISIS KESESUAIAN PENERIMAAN, PENYIMPANAN DAN PENDISTRIBUSIAN VAKSIN IMUNISASI DI DINAS KESEHATAN BONTANG - Iin Noviyanti (Journal of Innovation Research and Knowledge, 2025)
Vaccines are highly susceptible to damage; therefore, vaccine management requires special handling. Improper handling of vaccines can lead to vaccine damage. CDOB is a method of distributing drugs and/or drug substances aimed at ensuring quality throughout the distribution process in accordance with the required standards and intended use. This study aims to provide an overview of the types of immunization vaccines available at the Dinas Kesehatan Bontang and assess the compliance of vaccine reception, storage, and distribution at the Dinas Kesehatan Bontang with CDOB Guidelines. This research is classified as a qualitative observational descriptive study with a cross-sectional research design. Data collection was conducted through field observations using a checklist, document reviews, and interviews. The qualitative data obtained were analyzed descriptively to illustrate the actual conditions of the vaccine reception, storage, and distribution system. The compliance of vaccine storage and distribution was calculated using the compliance formula. The types of immunization vaccines available at the Dinas Kesehatan Bontang include BCG, MR, Hepatitis B (Uniject), IPV, TD, DT, Hepatitis B Imunoglobulin and Rotavirus.. The compliance rates for vaccine reception, storage, and distribution at the Dinas Kesehatan Bontang based on CDOB Guidelines were 100%, 63.2%, and 83%, respectively